2011
DOI: 10.4097/kjae.2011.61.5.388
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nitroglycerin on hemodynamic changes during laparoscopic low anterior resection

Abstract: BackgroundMore laparoscopic low anterior resections (LAR) are being performed in recent years. There has been controversy around the hemodynamic changes affected by the Trendelenburg position and pneumoperitoneum during LAR. The goal of this study was to analyze the effect of nitroglycerin (NTG) on hemodynamic changes during LAR.MethodsForty ASA physical status I-II patients undergoing LAR were randomized into two groups: the NTG infused group (N group, n = 20) and the control group (C group, n = 20). Anesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…By contrast, Jeon (14) demonstrated that adding nitroglycerin to lidocaine did not alter hemodynamic variables such as blood pressure. However, another study suggested that nitroglycerin infusion had partially successful hemodynamic effects during laparoscopic low anterior resections (15) Derakhshan et al (16) investigated the effects of nitroglycerin on pain control and reported that it decreased both systolic and diastolic blood pressure. This decrease might be due to nitroglycerin vasodilatation and lower vascular resistance by hypotension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, Jeon (14) demonstrated that adding nitroglycerin to lidocaine did not alter hemodynamic variables such as blood pressure. However, another study suggested that nitroglycerin infusion had partially successful hemodynamic effects during laparoscopic low anterior resections (15) Derakhshan et al (16) investigated the effects of nitroglycerin on pain control and reported that it decreased both systolic and diastolic blood pressure. This decrease might be due to nitroglycerin vasodilatation and lower vascular resistance by hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Jeon ( 14 ) demonstrated that adding nitroglycerin to lidocaine did not alter hemodynamic variables such as blood pressure. However, another study suggested that nitroglycerin infusion had partially successful hemodynamic effects during laparoscopic low anterior resections ( 15 )…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal muscle relaxation is an important confounding factor as inadequately relaxed muscles can cause an increase in IAP with consequent effects on haemodynamics. 8 None of the studies so far have monitored the degree of neuro muscular paralysis. We used a TOF monitor as an objective method of maintaining neuro-muscular paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Pharmacological agents like β-blockers, opioids, nitroglycerine and dexmedetomidine have been used to minimize such derangements with varied results. [5][6][7][8][9] Nitroglycerine (NTG) is commonly used as a rescue measure for intraoperative hypertension. 10,11 Clonidine, an -2 adrenoreceptor agonist, reduces sympathetic outflow and is advantageous in laparoscopic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The heart rate became normalized within 30 minutes. Moon et al 17 found partially successful hemodynamic effects with nitroglycerin infusion during laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%